Which comes first? Modeling the longitudinal association between mindfulness and neuroticism. (January 2022) - Wang, Huihui; Wang, Mengcheng; Wen, Zhonglin; Wang, Yang; Fang, Junyan
Abstract: Mindfulness-based interventions have been found to mitigate neuroticism. However, the temporal order of these relationships in non-clinical individuals without mindfulness training remains unclear. This four-wave longitudinal study examined whether within-person changes in mindfulness precede or follow changes in neuroticism in a large sample of Chinese college students (Wave 1: M age  = 21.12 ± 1.45, 60.7% female, N  = 1074). Using a random intercept cross-lagged panel model, we found a reciprocal association between mindfulness and neuroticism at the within-person level, which corroborated the dynamic personality theories. Changes in mindfulness were negatively correlated with subsequent changes in neuroticism ( B  = −0.11, p  < .001, β  = −0.11 to −0.09); and changes in neuroticism were also negatively correlated with subsequent changes in mindfulness ( B  = −0.14, p  < .001, β  = −0.15 to −0.11). At the between-person level, higher neuroticism was correlated with lower mindfulness ( r  = −0.51, SE = 0.04, p  < .001). These findings suggest that RI-CLPM modeling techniques are suitable for interpreting mindfulness and neuroticism associations both at the between- and within-person level. Highlights: Examined longitudinal associations between mindfulness and neuroticism. Found mutual within-person associations between mindfulness and neuroticism. Revealed a constant trait overlap of these two concepts at the between-person level.